Legal Reformulation on Expired Provisions of Prosecution of Tax Crimes in Indonesia - Situmorang, Parulian (Journal of Tax Law and Policy, 2023)
There are still philosophical gaps and juridical gaps in terms of the formation and implementation of Article 40 of the Law on General Provisions and Tax Procedures in Indonesia (KUP Law). Those gaps show the need for ideal regulation of the expiry date for prosecuting criminal offenses in the field of taxation in Indonesia in the future. Based on normative juridical methods using secondary data in the form of primary, secondary and tertiary legal materials, this study produces two conclusions. First, the expiry date for prosecuting criminal acts in the field of taxation currently in force in Indonesia has legal uncertainty due to explanations that do not interpret prosecution correctly. Apart from that, there are other criminal provisions in the field of taxation which are not related to "tax payable, the end of the Tax Month, the end of Part of the Tax Year, or the end of the Tax Year", and the different threats of imprisonment for criminal offenses in the field of taxation as if the prosecution has expired can also be interpreted as being attached to Article 40 of the KUP Law. Second, the ideal regulation of the expiry date for prosecuting criminal acts in the field of taxation in Indonesia in the future is that the provisions must fulfill the principles of equality before the law, legal certainty and human rights. It is recommended that there be alignment with the renewal of Article 40 of the KUP Law with the prosecution expiry provisions in the Criminal Code Law.